2020
DOI: 10.3389/fmolb.2020.596945
|View full text |Cite
|
Sign up to set email alerts
|

Surveying the Side-Chain Network Approach to Protein Structure and Dynamics: The SARS-CoV-2 Spike Protein as an Illustrative Case

Abstract: Network theory-based approaches provide valuable insights into the variations in global structural connectivity between different dynamical states of proteins. Our objective is to review network-based analyses to elucidate such variations, especially in the context of subtle conformational changes. We present technical details of the construction and analyses of protein structure networks, encompassing both the non-covalent connectivity and dynamics. We examine the selection of optimal criteria for connectivit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 88 publications
(148 reference statements)
2
12
0
Order By: Relevance
“…These new unique hubs at the S1-S2 interfacial regions in combination with the common hubs in the N2R linker region (T315, F318, R319, and R328) form a subnetwork that stabilizes connections between the NTD and RBD regions and the CTD1 and CTD2 domains. Similar to other network-centric analyses of the SARS-CoV-2 S trimers (Halder et al, 2020) we observed some variance in the distribution of hubs in different protomers due to the inherent asymmetry in the residue interaction networks across subunits. Structural maps of the network hubs on the structures of the S-D614 and S-G614 mutant trimers highlighted the broad distribution of mediating residues across S1 and S2 domains (Figure 8).…”
Section: Network Modeling Reveals Mutation-induced Reorganization Of the Residue Interaction Network In The Open Statessupporting
confidence: 85%
See 2 more Smart Citations
“…These new unique hubs at the S1-S2 interfacial regions in combination with the common hubs in the N2R linker region (T315, F318, R319, and R328) form a subnetwork that stabilizes connections between the NTD and RBD regions and the CTD1 and CTD2 domains. Similar to other network-centric analyses of the SARS-CoV-2 S trimers (Halder et al, 2020) we observed some variance in the distribution of hubs in different protomers due to the inherent asymmetry in the residue interaction networks across subunits. Structural maps of the network hubs on the structures of the S-D614 and S-G614 mutant trimers highlighted the broad distribution of mediating residues across S1 and S2 domains (Figure 8).…”
Section: Network Modeling Reveals Mutation-induced Reorganization Of the Residue Interaction Network In The Open Statessupporting
confidence: 85%
“…Notably, the closed and open forms of the S-D614 and S-G614 structures can share a number of conserved hub positions that are largely determined by the topology of the spike trimer (Figure 7C). Interestingly, these common hubs are very similar to the conserved network hubs reported for cryo-EM structures of the SARS-CoV-2 spike S trimer in the closed state (K986P/ V987P,) (pdb id 6VXX) and open state (pdb id 6VYB) (Halder et al, 2020). Among conserved hub positions are residues proximal or directly aligned with the hinge sites shared by closed and open forms including T315, F318, R319, R328, V539, F592, and Y612 located near the D614 mutational site.…”
Section: Network Modeling Reveals Mutation-induced Reorganization Of the Residue Interaction Network In The Open Statessupporting
confidence: 76%
See 1 more Smart Citation
“…While some previous studies have implemented similar network-based approaches to on relatively shorter simulations with the aim of identifying overall subdomains and hubs in the Spike [55][56][57], our analysis provides detailed and new insights into the communication structure and the control cores of the protein at large. We identify a critical communication ring connecting peripheral regions of the protein, such as the NTD supersite, the up-RBD, and the furin cleavage sites, to each other as well as to the core of the protein, where crucial processes take place upon host receptor binding (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This analysis provides also a global metric to measure changes in connectivity and interaction between subdomains and inter-protomer association in the SARS-CoV-2 S structures. 95…”
Section: Dynamic-based Modeling Of Residue Interaction Network and Community Analysismentioning
confidence: 99%